The Ecology of the Tropical Salamander, Bolitoglossa subpalmata, in Costa Rica - Vial, James L. (1967)
An intensive field shldy was conducted on the montane tropical salamander, Bolitoglossa subpalmata (Boulenger) in the Cordillera de Talamanca of Costa Rica. Information was obtained on over 4,000 specimens from quadrats, random samples and from six marked populations. Measurements of the physical environment and laboratory experiments supplemented the field data. The results and conclusions of the study are as follows:1. The vertical distribution of the species extends fram approximately 1,375 m to over 3,200 m; however, below 2,400 ro the distribution is localized and densities are very low. Tropical vegetation formations characteristically inhabited by B. subpalmata include the Tropical Lower Montane Wet Forest and the Tropical Montane Rain Forest. Clay crevices, depressions under logs. rocks and moss, as well as the arboreal habitat, are utilized by this nocturnal salamander on the Cerro de la Muerte. Although the major distribution pattern of the species seem, to be determined by thermal limits. the type of habitat selected is influenced by temperature and moisture in both elevational and seasonal occurrence.2. Microscope slides of gonadal tissue show continuos sperm production in adult males. The lobular formation of testes is similar to that which has been described for Desmognathus. Females prabably require about two years to complete a cycle of oviposition, although at any time sorne individuals in the population are in a reproductive stage. Convoluted oviducts are retained thraughout the life of the mature female.3. B. subpalmata usually nests under racks and debris in well protected sites. The selected sites permit avoidance of both excessively wet or dry conditions and have a stability of temperatures between about 10 to 16° C. which appears to be the optimal range (the upper level may be ecologically critical). Usually the size of a nesting site restricts its occupatlon to but one clutch; however, up to three egg masses with their attending adults have been found in a single "nursery".4. Unstalked eggs are deposited singly or in a series of two to four. If not situated in a grape.like cluster at the time of laying. the ovipositing female may actively gather them together. The clutch averages 23 eggs and is not fixed to any object. The eggs are about 5 mm in diameter and cohere by the outer membranes. Persistent, but not constant, attendance of an adult is required for sustained development. Both males and females have been abserved to brood the clutches.5. After the estimated four to five month period required for development, a completely transformed young ruptures the two enclosing membranes by violent body contortions. Shortly after emergence it retreats to protective cover. For the first two years growth is reJatively rapid. probably about 5 mm per year, after which ít reduces to a fairly constant calculated average of approximately 3 mm per year. No sexual differences in growth rates are known.6. The species is active throughout much of the night, however the patterns of activity are variable and influenced by temperature and, more frequently, by humidity. Maximum activity levels appear at temperaturcs aboye 6° C and relative humidities of more than 80%, and are somewhat reduced at times of actual precipitation. Probably between 10 and 25% of the near-surface population is active during any given night.7. Vagility in B. subpalmata is limited and individuals utilize a definite home range. No statistically significant differences were found in the movements of males, females and juveniles either in distance or in frequencies. The average home range area for all of these groups is 44 sq. m. There is no evidence of any homing behavior in displaced individuals.8. Aggregations appear to be a response to unfavorable environmental conditions and are not related to reproductive behavior. Avoidance of extremely dry or wet conditions results in congregation at the most favorable habitat sites.9. Densities of B. subpalmata on the Cerro attain striking proportiom and are locally controlled by density-independent factors. Population densities are correlated with elevation; the greatest densities are found near the summit and in this area may exceed 9,000 animals per hectare (3,690 per acre). Both local and seasonal changes in moisture influence the occurrence of animals at the surface and during the dry periods they retreat to Sub-surface cover.10. Age class estimates of populations, admittedly speculative, are based on the measured hatchling size and calcub.ted growth rates. The maximum age attained is about 18 years. Sexual maturity is apparently attained by males in the sixth year although it is not until the twelfth year that móst females have deposited eggs. Males probably not only mature more rapidly, but reach senility earlier than females. The expected one-to-one sex ratio occurs at all seasons and throughout all age groups except the oldest, in which females notably exceed males.11. Observations of numbers of egg clutches and spent females are used for determining the estimated annual partíal potential reproductive capacity of 58%.12. Survivorship and mortalíty estimates, computed by different mathematical procedures, are variable to a degree that casts serious doubts upon the application of most of these methods to salamander populations. The fluctuation of population densities, extensive use of the habitat, and low activity levels contribute to problems in using recapture records. The consistent absence of immahue animals in the samples presents almost insurmountablc problems in using single capture data.13. The best available annual survivorship estimates are between 0.29 and 0.65, decreasing with age. It has not been feasible to construct life tables or survivorship curves. The potentially high reproductive capacity and low observed mortality factors acting upon adults suggest a high juvenile and egg clutch mortality. A high mortality rate of eggs is further indicated by the absence of strong attendance fidelity on the part of adults and lack of homing behavior in B. subpalmata.14. Moisture requirements of the species are similar to several extra-tropical plethodontids. The total body moisture averages about 80% of body weight. No behavioral stress is noted in animals losing up to 32.3% of initial body weight, although none survived a loss of more than 41.2%. Rates of water loss averaged 2.5% per hour, but are somewhat higher in smaller animals. Loss rates in all individuals are redueed by aggregation behavior. Rehydration is accomplished up to six times more rapidly than dehydration at the same temperatures. Rates of water resorption in saturated conditions are less than that of an individual when submerged, but the latter environment offers little, if any, ecological advantage.15. Periods at which the loss of righting ability occurred under submerged conditions ranged from 3.50 to 7.75 hours (average 5.35), and cessation of capillary circulation was noted at from 6.75 to 17.50 hours (average 10.14). The average differenee between these periods was 3.30 hours.16. Soil moistuce exerts a great influence on sulface occupation of the habitat areas. Salamanders are virtually absent at less than 30%, the optimum range being between 55 and 75%.17. Adult B. subpalmata can survive prolonged exposure to temperatures between 4 and 24° C. At below freezing temperatures (- 4.0 C) death usually results after less than two hours exposure. Temperatures of 27° C are lethal after 72 hour;, while lethal thermal shock is almost immediate at 37° C.18. Ecological thermal limits are probably at a sustained level of about 16° C, above which no eggs were laid. The critical thermal maximum (CTM) of approximately 37° C is here considered as a physiological, rather than an ecological, maximum and not the limit of tolerance at the most susceptible stage of the life cycle.19. Dody temperatures show little variation from those of the microhabitat: The range of voluntarily tolerated temperatures of from 2.8 to 23.8° C (a differenee of 21°) is greater than that reported for any other plethodontid species.20. Temperate zone plethodontids occupy a wider varicty of babitats than those in the tropics. None of the latter are known to be aquatic. Probably there has been little selective advantage in returning to water after the evolution of direct development. B. subpalmata is not exceeded in its habitat utilization by any single species in the family.21. Doth tropical and extratropical plethodontids are generally absent from areas where annual precipitation is less than potential evapotranspiration, except where these are modulated by local conditions. Minimum temperature limits are probably close to the 6° C biotemperature level. Altitudinal patterns of distribution in various tropical species indicate adaptations to different thermal levels.22. Three types of reproductive patteros are exhibited in plethodontid genera. Desmognathus includes species in all of these patterns. It is very probable that all tropical species, like B. subpalmata, have direct development.23. Extratropical plethodontids have notably staggered breeding periods, both as populations and as distinct species. Acyclic reproduction in B. subpalmata maximizes use of available nesting sites and permits evasion of short-term unfavorable physical changes in fue environment at fue population level.24. Testicular lobing apparently is a manifestation of limits imposed by metabolic capacities of the primordial germ tissue and is not correlated with environmental periodicity. Biennial oviposition is limited by similar intrinsic conditions.25. It is suggested that of the probable multiple functions of brooding behavior, manipulation of the eggs by the adult satisfies a vital kinetic requirement that prevents developmental adhesions, thus being in part, analagous to an amnionic funtions.